CHICK LIT DALAM DUNIA SASTRA INDONESIA - Kasno Kasno; Erlis Nur Mujiningsih (Pujangga: Jurnal Bahasa dan Sastra, 2016)
ABSTRACTChick lit is a kind of literary works aimed at independent single young women is like the slogan printed on theoutside front cover. To learn more about chick lit, this study aims to describe the beginning of chick lit in theworld of Indonesian literature. This study uses a qualitative description to give an aid for the readers to knowwhat is happening in the environment, under observation, such as what the participants' point of views, eventsand activities occuring in the setting. Theory referenced in this study is the theory of Seger‟ receptionaesthetics , which states that the aesthetic reception views the value of literature as a concept of constantchange depending on the system of readers‟ norms . The analysis conducted to describe the history of theemergence of chick lit, the style of the author (authorship), and Indonesian readers‟ response . Theconclusion is that novels classified as chick lit written by women and aimed at female readers. Readers of thenovels are indeed mostly women, both women of mature aged and those who can be classified as beginnerreaders.Keywords: literature, style of the authors, women, beginner reader